“When I Look in the Mirror, I Want to See a Healthy Body”: The Lived Experience of Young Previvors, Bilateral Risk-Reducing Mastectomy, and Body Image - Christa Torrisi; Mei R. Fu; Michelle Teti; Jane M. Armer (Global Qualitative Nursing Research)
Breast cancer is a significant cause of cancer death in young women in the United States. Inherited pathogenic variants, like BRCA1 and BRCA2, contribute to an increased lifetime breast cancer risk in this population. For women with a known pathogenic variant but without a previous cancer diagnosis, also known as “previvors,” the bilateral risk-reducing mastectomy (BRRM) most effectively reduces breast cancer risk. However, this surgery often causes physical change to the body. While existing research has examined the effect of BRRM and body image among previvors across the lifespan, the effect of prophylactic breast removal to decrease lifetime breast cancer risk in young previvors less than 40 years of age is less understood. A descriptive phenomenological approach, along with participant-submitted images, from a sample of 13 young previvors from the Midwestern United States, aged 29 to 39, explored the lived experience of BRRM and body image in the first 12 months following surgery. Narrative data served as the primary source, augmented by participant-submitted visual data. Essential themes were intuited to include BRRM to promote health, the importance of adaptation and acceptance to a changed body, and unexpected challenges following surgery; body image was found to be largely positive after healing occurred.